Comparative Analyses of Physicochemical Properties of Artisanal Refined Gasoline and Regular Automotive Gasoline - Udo, Godwin J.; Awaka-Ama, Joachim J.; Uwanta, Emaime J.; Ekwere, Ifiok O.; Chibueze, Igwe R. (Frontiers in Chemistry, 2020)
Physicochemical properties of artisanal refined gasoline (ARG) and regular automotive gasoline (RAG) sampled from the Eastern Obolo Creek and Mkpat Enin, Akwa Ibom State, Nigeria were investigated. This was to compare the physicochemical properties of the two gasoline samples with each other and their compliance with American Society for Testing and Materials (ASTM) standards. The finding revealed an antiknock index of RAG (91.15%) and ARG (83.05%), atmospheric distillation of RAG (185°C) and ARG (184°C), Reid vapor pressure of RAG (0.53 kg/cm3) and ARG (0.36 kg/cm3), gravity of RAG (0.771) and ARG (0.683), sulfur content of RAG (0.014%/wt) and ARG (0.02%/wt), while Flash point for RAG were Pensky Martens −25°C, Abel-Pensky −33°C and ARG Pensky Martens −27°C, Abel-Pensky −35.36°C, respectively. The research octane number, motor octane number, Reid vapor pressure, sulfur content, and specific gravity of RAG were (ASTM) compliant while only the final boiling point and sulfur content of ARG were within ASTM range. Based on the findings, the LRG might have been poorly refined or adulterated and could constitute problems in automotive engines if used. However, this crude technology can be upgraded and the gasoline quality improved through alkylation, isomerization, and cyclization. Artisanal refiners should be trained to become proficient with the intent of becoming incorporated into the upstream petroleum sector.